Development of a Simple IFN-γ Release Whole Blood Assay for the Assessment of Leishmania infantum Specific Cellular Immunity in Dogs - Anna Sára Molnár; Andrea Murillo-Picco; Clara Jiménez-Fortunato; Laia Solano-Gallego (Animals)
Canine leishmaniosis (CanL) is a zoonotic disease caused by Leishmania infantum, where increased interferon-gamma (IFN-γ) levels are associated with controlling the infection and mild to moderate disease. Therefore, monitoring IFN-γ concentrations is essential for monitoring the immune responses in CanL. This study compared a faster, cost-effective IFN-γ release whole blood assay in tubes (WBA-T) with a standardized version (WBA-S) in 41 dogs at different states of L. infantum infection. WBA-T was performed at 24, 48, and 72 h of incubation with three conditions: blood, blood with L. infantum-soluble antigen (LSA), and blood with mitogen ConA. WBA-S was performed in plates, with blood diluted and incubated for five days using the same conditions. Supernatants (WBA-S) or plasma (WBA-T) were harvested for IFN-γ measurement by ELISA. No significant differences were observed in terms of IFN-γ concentration between WBA-T and WBA-S under LSA conditions. However, the 48 h incubation period during WBA-T showed the highest median of IFN-γ concentration compared to other incubation periods and WBA-S. The IFN-γ concentrations under ConA stimulation in WBA-S were significantly higher than in WBA-T at all incubation times studied. In conclusion, WBA-T stimulated with LSA at 48 h incubation time was shown to be the most appropriate for assessing IFN-γ production.